Rapid discrimination of Enterococcus faecium strains using phenotypic analytical techniques. Issue 42 (19th October 2016) - AlMasoud, Najla; Xu, Yun; Ellis, David I.; Rooney, Paul; Turton, Jane F.; Goodacre, Royston
Abstract : Clinical isolates of glycopeptide resistant enterococci (GRE) were used to compare three rapid phenotyping and analytical techniques. Abstract : Clinical isolates of glycopeptide resistant enterococci (GRE) were used to compare three rapid phenotyping and analytical techniques. Fourier transform infrared (FT-IR) spectroscopy, Raman spectroscopy and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) were used to classify 35 isolates of Enterococcus faecium representing 12 distinct pulsed-field gel electrophoresis (PFGE) types. The results show that the three analytical techniques provide clear discrimination among enterococci at both the strain and isolate levels. FT-IR and Raman spectroscopic data produced very similar bacterial discrimination, reflected in the Procrustes distance between the datasets (0.2125–0.2411, p < 0.001); however, FT-IR data provided superior prediction accuracy to Raman data with correct classification rates (CCR) of 89% and 69% at the strain level, respectively. MALDI-TOF-MS produced slightly different classification of these enterococci strains also with high CCR (78%). Classification data from the three analytical techniques were consistent with PFGE data especially in the case of isolates identified as unique by PFGE. This study presents phenotypic techniques as a complementary approach to current methods with a potential for high-throughput point-of-care screening enabling rapid and reproducible classification of clinically relevant enterococci.